The bakla and gay globality in Philippine mainstream and independent cinema - MICHAEL, INTON (Archīum Ateneo, 2012)
This paper explores representations of the bakla and gay globality in Philippine mainstream and independent films. This study looks at how the bakla is performed through the four components of effeminacy, cross-dressing, same-sex sexuality (desiring the o